Photochromic holo-cellulose wood-based aerogel grafted azobenzene derivative by SI-ATRP. (1st May 2021) - Li, Ming; Fu, Shiyu
Graphical abstract: Highlights: The wood was delignified to prepare holo-cellulose wood-based aerogel. An unexpected photochromic wood aerogel was firstly fabricated via SI-ATRP. The modified wood aerogel still has good compression resilience. Modified wood aerogel shows reversible photochromic behavior under UV and sunlight. Abstract: Wood is actually a natural polymers composite that is easy to process, mainly constituted of cellulose, hemicellulose and lignin. However, most wood-based functional materials are prepared by physical methods, which undoubtedly limit the application of wood-based materials. Herein, the wood aerogel (WA) was obtained from wood by delignification and freezing dried. The WA then was fabricated into an unexpected photochromic wood aerogel (PWA) via surface-initiated atom transfer radical polymerization (SI-ATRP) covalently grafting poly{6-[4-(4-methoxyphenyl-azo)phenoxy]hexyl methacrylate} (PMAZOM). Both WA and PWA showed good compression resilience. The hydrophobicity of PWA was obviously enhanced because of the surface modification. The color of PWA can change from yellow to orange-red after being irradiated by UV light for 30 s. The color of sample can be reversibly changed to yellow under sunlight for 200 s. The lightweight and photosensitive wood aerogel is potential to apply for optical information storage materials and photosensitive devices.